Optimization of Indoor Airflow Distribution in Variable Refrigerant Flow Air Conditioning System: A Review (International Journal of Engineering Materials and Manufacture, 2025)
Variable Refrigerant Flow (VRF) air conditioning systems have gained widespread acceptance for their energy efficiency, precise temperature control, and flexibility in multi-zone applications. However, the optimization of indoor airflow distribution remains a critical factor for enhancing system performance and occupant comfort. This review synthesizes the current research on the strategies and methodologies employed to optimize the indoor airflow distribution in VRF systems. Key areas of focus include advanced sensor integration, computational fluid dynamics (CFD) modeling, and the impact of indoor unit placement and design of the system. Studies highlight the importance of adaptive control strategies that respond to real-time occupancy and thermal load variations. Additionally, advancements in sensor technology and CFD simulations offer detailed insights into airflow patterns and temperature distributions, facilitating more effective system design and operation. This review also identifies the existing gaps in the literature and suggests the future research directions, emphasizing the need for integrated approaches that combine empirical data and advanced control mechanisms to achieve the optimal indoor air quality and the energy efficiency in the VRF systems. It is found that the VRF system is more economic and efficient such that the VRF system is found to have 44% cost profit when compared with the conventional HVAC system. On the other hand, the energy saving obtained with solar energy based VRF for the hot-dry climate is 17.5% and 11.6% against conventional all-air VAV and VRF systems, respectively. Furthermore, the proposed control strategy can improve energy efficiency by 12.6% and control room temperature fluctuations within ± 0.5°C.